Assessment of Soil Thermal Properties in a Tropical Environment: Ile Ife and Ibadan (2011)
Soil thermal properties are crucial parameters that affect soil heat flux. Time series of soil temperature, soil moisture content, and rainfall and soil heat flux were measured at two tropical locations in West Africa during the transition from dry to wet season, and at the peak of rainy season in July. The data were analyzed to estimate soil thermal diffusivity, thermal inertia and volumetric heat capacity. The thermal properties were clearly related to soil moisture (and thus rainfall) throughout the measurement period. The modeled soil heat flux using the soil thermal properties compared favorably with the measured soil heat flux.